INFUSA DAUN PACING Costus speciosus (Koen.) J.E. SMITH SEBAGAI PENGHAMBAT JUMLAH DAN KUALITAS SPERMATOZOA PADA MENCIT JANTAN BALB/C - Ika Puspita Sari; Siti Rahayu; Dicky M. Rizal (Majalah Obat Tradisional, 2013)
Costus speciosus (Koen.) J.E. Smith (Pacing) is a plant widely use as traditional contraception. The objective of this study is to evaluate the effect of pacing leaves infusion on Balb/C mice spermatogenesis and its reversibility. This study was conducted on male mice. Mice was divided into 6 groups, 6 mice each group. Pacing leaves infusion was given orally at dose 275, 550, and 1100 mg/kg body weight for 14 days. The control groups received distilled water and another group received corn oil and andriol 5.2 mg/kg body weight. At day 15, 3 mice from all of groups was euthanized and the rest of mice in all of groups was euthanized in day 28 to evaluate the reversibility of spermatogenesis. The observation of spermatogenesis was conducted on quantity and quality of spermatozoa (motility, viability, and morphology). The result showed that pacing leaves infusion at dose 275, 550, and 1100 mg/kg body weight reduced the number of spermatozoa by 16-38 % (p<0.05), but it did not change the viability and morphology of the spermatozoa. At dose 275 and 550 mg/kg body weight, pacing leaves infusion reduced the motility of spermatozoa by 36-39 % (p<0.05). The ability of pacing leaves infusion in reducing the number and motility of spermatozoa is reversible.